Application of seasonal freeze-thaw to pretreat raw material for accelerating green waste composting. (1st June 2019) - Yu, Kefei; Li, Suyan; Sun, Xiangyang; Cai, Linlin; Zhang, Pengfei; Kang, Yue; Yu, Zhihao; Tong, Jing; Wang, Lin
Abstract: The recalcitrance of green waste, caused by its high lignocellulose content, is a technical challenge for accelerating green waste composting. However, because lignocellulose degradation in litter (similar to green waste) can be promoted during the freeze-thaw season, and the composting is difficult to implement in this period (due to the low temperature); seasonal freeze-thaw was intended to be used as a pretreatment strategy for the existing technical challenge in the winter of cold regions. In this process, green waste was pretreated with seasonal freeze-thaw to enhance its lignocellulose degradation for subsequent composting. To verify this assumption, two strategies for the pretreatment were used: the green waste was either drenched or immersed in water during the freeze-thaw season, and the effects on subsequent composting were evaluated. The results demonstrated that both strategies can significantly promote the mineralization of TOC (total organic carbon, by 2.73%–8.01% compared with the control, the following comparisons were all based on the control), TN (total nitrogen, by 0.21%–0.52%), and lignocellulose (lignin degradation was promoted by 3.52%–3.73%, cellulose degradation was promoted by 13.23%–14.26%) during composting and that the synthesis of humus was also enhanced (by 19.19%–21.43%). Furthermore, since the loss of NH 4 + N and NO 3 − N was significantly less in the drenched treatment than in the immersed treatment (by 9.15% for the loss of NH 4 + N and 7.66% for the loss of NO 3 − N), drenching the green waste during the freeze-thaw season might be a better strategy than immersing for nitrogen conservation. An additional advantage of drenching compared to immersing is water conservation. Highlights: Effect of seasonal freeze-thaw pretreatment on green waste composting was studied. Seasonal freeze-thaw improves biodegradation during green waste composting. Seasonal freeze-thaw increases mineral nitrogen loss during green waste composting. Seasonal freeze-thaw promotes humification during green waste composting.